Incentives and Opportunities to Manage Earnings around Option Grants* - Baker, Terry A.; Collins, Denton L.; Reitenga, Austin L. (Contemporary Accounting Research, 2009)
This study examines discretionary accruals imbedded in quarterly earnings announcements that precede executive stock option grants. Prior research indicates that managers attempt to increase the value of their option pay (by depressing the option's exercise price) through a variety of strategies including timing voluntary disclosures, influencing option grant dates, or managing accruals. This study extends the research by jointly examining managerial incentives and opportunities to pursue an accruals-based strategy. We find evidence that discretionary accruals are lower when option pay is high and when concurrent firm performance is poor (incentive factors), but only when firms issue grants following earnings announcements relatively infrequently (opportunity factor). For firms that follow a predictable grant schedule, managers behave as if they believe that investors will discount earnings-based signals preceding the grant. Our results suggest that the decision to pursue an option-related strategy is influenced by economic tradeoffs. From a policy perspective, our results have relevance for the ongoing debate over option compensation practices, appropriate disclosure to investors, and the quality of corporate earnings.